A morte visível e a vida invisível: um estudo sobre o assentamento de Exu e a Paisagem Sagrada da Enseada de Água de Meninos, Salvador (Bahia) - Novaes, Luciana de Castro Nunes (2013)
The goal of this study is to give an archaeological comprehension of Água de Meninos Bay (Salvador/Bahia) as a sacred site, formed by layers of material and intangible meanings, due to the submerged presence of an iron structure attributed to Exu. Thus, the intentional presence of a religious structure characterizes this space as a historic site, making it possible to think of the processes of religious appropriation of the landscape, the handling of the materiality and the construction of diasporic realities on the New World. Exu possesses mythical powers related to trade and communication, presently worshipped on the extension of Benin Gulf and in the Afro Brazilian religions, the deity is considered to be the protector of fairs and markets as well as the patron of the circulation of goods and knowledges. The religious structure was found near the Ferry Boat station. The Ferry-Boat station site is located between the historical region where successive fairs took place in the 19th and 20th centuries and the Salvador sea Port, which is at work since the 16th century on Água de Meninos. Therefore, the Archaeology of Religion was taken as the theoretical and methodological field to be applied in the problematization both of the afro-religious material culture and the Bay s landscape, in order to allow the ritualistic, religious and sacred aspects Bahian Afro descendant populations to acquire archaeological sense and meaning.